Barcode reader usage: UiTM student's acceptance / Hasrulliza Abd Halim - Abd Halim, Hasrulliza (2006)
These researches are defining the problem and identifying the acceptance of barcode reader system usage among UiTM student for PTAR borrowing books transaction. This research began with the face-to-face interview with the librarian to identify the problems of the current system. From the interview we found many weaknesses and problems occurring in the current system. In PTAR, currently they have two methods in borrowing books system; self-machine system and counter / manual system. Nowadays UiTM library has five self-machines which are at PTAR 1, PTAR2, PTAR3, FSPU and Puncak Perdana. In UiTM we have two version of self-machine system. The first version of self-machine system does not have any security section such as password or ID and the second version has password but the password is unreliable because just take of student ID. The staff revealed that the self-machine system is not effective and PTAR should have other alternative system. The recommendation is to give students the freedom to choose their own password, if want to change the system that need big cost.